Organization of project activities in the system of advanced training of teachers - Kirillova, Inna K. (2020)
Project activity occupies an important place in the system of professional development. Focused on a rapidly changing environment, it provides the widest opportunities for innovative development of the field of additional education. The implementation of project activities allows you to form important for students of courses, leading decisions in the context of global educational competition and high uncertainty of the educational environment. The purpose of the article is to study the experience of organizing project activities in the system of professional development of teachers. Project activity is a joint educational creative activity of course participants that has a common goal and agreed methods to achieve it. The article reveals the experience of project activities of students in the framework of the course "Management in education". In the process of implementing project activities, the project competence of students is formed. Project activity occupies an important place in the system of professional development. Its implementation allows you to radically change the entire learning process, make it active, creative and independent.